On Butterflies and Frankenstein: A Dynamic Theory of Regulation - Johan F. M. Swinnen; Thijs Vandemoortele (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
There are major differences in regulation among various countries. A particular case is the difference between the EU and US in regulating biotechnology.We develop a firmal and dynamic model of government decision-making on regulation. We show that minor differences in consumer preferences can lead to important and persistent regulatory differences, and that temporary shocks to preferences can have long-lasting effects. This hysteresis in regulatory differences is shown to be caused by producer protectionist motives. We argue that this model may contribute to explain the difference between EU and US biotechnology regulation.
Keywords: 330